The Inclusion of technological tools In education - Asencio Linarez, Carlos Daniel; Mena Sorto, Otoniel Neftalí (2024)
This paper presents a report on the virtual tools of how they help in the educational field. Digital platforms or learning management systems allow students to access a wide variety of educational materials from anywhere and at any time. This has made it easier for students to learn at their own pace and in their own time, which can be especially enhanced for those who have difficulty attending school on a regular basis. In addition, creating virtual tools have allowed educators to personalize learning for each student, requiring a wide range of options for both synchronous and asynchronous to develop interactive activities. In short, they have guaranteed the accessibility and flexibility of learning, which has improved performance and the learning experience for both sides; teachers and students, bringing quality education to everyone who wants to excel and have a decent education in the modern age.